Pengaruh Reward dalam Teori Behavioristik terhadap Perilaku Anak - aprilia, rizka mega (Maliki Interdisciplinary Journal, 2026)
This article discusses the relevance of behaviorist theory in modern learning in the digital era, with a focus on the application of rewards as a primary strategy to shape positive behavior in children. Behaviorist theory, developed by Pavlov, Thorndike, and Skinner, emphasizes learning through stimulus-response and reinforcement, and remains significant in the context of digital education such as e-learning and gamification. The introduction examines how child development is influenced by character formation through rewards, which serve as reinforcement for extrinsic motivation, repetition of behavior, and conditioning of positive habits. The basic concepts of behaviorism are explained as an empirical foundation for structured instructional design, although they have limitations in overlooking cognitive aspects. The reward mechanism involves motivation, repetition, conditioning, and enhancement of self-efficacy, applied in schools through praise or points, and at home through simple rewards. Its benefits include improved discipline, motivation, social relationships, and internalization of values; however, risks such as dependency on rewards and decreased creativity need to be considered. Effective strategies include consistency, specificity, variation, and age-appropriate adjustments, as well as transitioning to intrinsic motivation. Overall, rewards as a behaviorist tool support holistic child development in the digital era, provided they are applied wisely to avoid limitations and maximize benefits.